Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.cognition.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

What makes a movement a gesture?

Abstract: Theories of how adults interpret the actions of others have focused on the goals and intentions of actors engaged in object-directed actions. Recent research has challenged this assumption, and shown that movements are often interpreted as being for their own sake (Schachner & Carey, 2013). Here we postulate a third interpretation of movement—movement that represents action, but does not literally act on objects in the world. These movements are gestures. In this paper, we describe a framework for predicting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 44 publications
3
47
0
2
Order By: Relevance
“…We suggest that there is a third category of movement--movement that is intended to represent goal-directed action--in other words, gesture. When a movement is produced in the presence of objects, but does not involve touching or moving the objects (e.g., a hand makes an arc motion from a ball to a box), adults tend to interpret that movement as a representation of goal-directed action (in this case, how the ball should be moved to the box) (Novack, Wakefield & Goldin-Meadow, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…We suggest that there is a third category of movement--movement that is intended to represent goal-directed action--in other words, gesture. When a movement is produced in the presence of objects, but does not involve touching or moving the objects (e.g., a hand makes an arc motion from a ball to a box), adults tend to interpret that movement as a representation of goal-directed action (in this case, how the ball should be moved to the box) (Novack, Wakefield & Goldin-Meadow, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The answer to these questions is in Hutchins' view one of engaging in specific culturally shaped perceptual processes of action, a sort of high-level cognitive processes that require meaning from movement. The view is supported by recent work that has been measuring to what extent contextual cues can make a movement into a gesture, and a gesture appear more meaningful, and subsequently can encourage onlookers to give representational responses for bodily actions (Novak et al 2016). The results from Novak et al (2016) revealed the impact of external cues to the interpretation of bodily action, where the meaning can be enacted from the environment within which the embodied action occurred.…”
Section: The Role Of Gestures In Distributed Cognitionmentioning
confidence: 87%
“…The view is supported by recent work that has been measuring to what extent contextual cues can make a movement into a gesture, and a gesture appear more meaningful, and subsequently can encourage onlookers to give representational responses for bodily actions (Novak et al 2016). The results from Novak et al (2016) revealed the impact of external cues to the interpretation of bodily action, where the meaning can be enacted from the environment within which the embodied action occurred. They also suggested that the onlooker's prior knowledge of a particular object might affect the ability to use the particular object to interpret a movement as representational as well as cues that indicate that the embodied action is part of a communicative act (e.g., the specific content of the speech, facial expressions and eye-gaze).…”
Section: The Role Of Gestures In Distributed Cognitionmentioning
confidence: 87%
See 2 more Smart Citations